Late Talker - Early Intervention for children being at risk of language disorder - Dohmen, A; Vogt, S (2006)
Detection and intervention of Late Talkers are of rising importance in German-speaking countries during the past years. One reason for this is that the knowledge about normal language development and possible deviations has grown. Thus criteria have been described and instruments developed to detect children being at risk of language disorder at an early age. On the other hand methods to work with very young children were established. The present article provides an overview about possibilities to detect late talking children. Furthermore, it describes intervention methods and implementation. The main aim is the description of targets within early intervention on the four language levels (phonology, semantics/vocabulary, syntax/morphology, pragmatics).